2005
DOI: 10.1002/pen.20401
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and rheological properties of mLLDPE/LDPE blends

Abstract: The thermal and rheological properties of two types of metallocene-catalyzed linear low-density PEs (mLL-DPEs) and two LDPEs, as well as their blends, were studied using differential scanning calorimeter (DSC) measurements and rheometry. The DSC results showed that the mLLDPE-1 based on the hexene comonomer is immiscible with both LDPEs in crystalline states, whereas the mLLDPE-2 based on the octene comonomer is miscible with the LDPEs. This suggests that increasing the length of short chains in mLLDPEs can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 33 publications
2
52
0
Order By: Relevance
“…[1][2][3][4][5][6][7] However, this enhancement of processing and properties is dictated by phase homogeneity or heterogeneity of these blends in the melt and solid state. A large number of studies utilizing different techniques were devoted to investigate the phase morphology and characterization of polyolefin blends.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5][6][7] However, this enhancement of processing and properties is dictated by phase homogeneity or heterogeneity of these blends in the melt and solid state. A large number of studies utilizing different techniques were devoted to investigate the phase morphology and characterization of polyolefin blends.…”
mentioning
confidence: 99%
“…A large number of studies utilizing different techniques were devoted to investigate the phase morphology and characterization of polyolefin blends. These techniques include transmission electron spectroscopy, [8][9][10][11] small angle neutron scattering, [11][12][13] differential scanning calorimetry, 2,5,11,[14][15][16][17][18][19][20][21][22][23] rheology, 3,4,6,7,[16][17][18][24][25][26][27][28][29][30] X-ray diffraction 11,14,31 and more recently thermal fractionation techniques. 33,34 Mechanical characterization of polyolefin blends has also been a subject of interest.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that the complex behavior of these blends can be understood by assuming the existence of two phases; one phase composed of the highly branched low Mw chains of both polyethylenes, and a second phase composed of the high Mw chains (mostly linear) of both polyethylenes. Differential scanning calorimetry (DSC) thermograms of LLDPE/LDPE blends reported by Fang [5] supported the existence of a third phase composed of chains from the two polyethylenes that have the ability to cocrystallize; additionally, enhancement in the crystallization behavior of BPE blended with linear polyethylene (LPE) was explained in terms of co-crystallization due to the incorporation of the linear segments of BPE into rich LPE lamellae and the segregation of the most branched chains.…”
Section: Journal Of Materials Science and Chemical Engineeringmentioning
confidence: 93%